Metabolic dysfunction-associated steatotic liver disease (MASLD) in children with obesity: An Obesity Medicine Association (OMA) and expert joint perspective 2025 - Jennifer Panganiban; Mohit Kehar; Samar H. Ibrahim; Phillipp Hartmann; Shilpa Sood; Sara Hassan; Charina M Ramirez; Rohit Kohli; Marisa Censani; Erin Mauney; Suzanne Cuda; Sara Karjoo (Obesity Pillars)
Introduction: This Obesity Medicine Association (OMA) Expert Joint Perspective examines steatotic liver disease (SLD), which is composed of metabolic dysfunction-associated steatotic liver disease (MASLD), and metabolic dysfunction-associated steatohepatitis (MASH) in children with obesity. The prevalence of obesity is increasing, rates have tripled since 1963 from 5 % to now 19 % of US children affected in 2018. MASLD, is the most common liver disease seen in children, can be a precursor to the development of Type 2 Diabetes (T2DM) and is the primary reason for liver transplant listing in young adults. We must be vigilant in prevention and treatment of MASLD in childhood to prevent further progression. Methods: This joint clinical perspective is based upon scientific evidence, peer and clinical expertise. The medical literature was reviewed via PubMed search and appropriate articles were included in this review. This work was formulated from the collaboration of eight hepatologists/gastroenterologists with MASLD expertise and two physicians from the OMA. Results: The authors who are experts in the field, determined sentinel questions often asked by clinicians regarding MASLD in children with obesity. They created a consensus and clinical guideline for clinicians on the screening, diagnosis, and treatment of MASLD associated with obesity in children. Conclusions: Obesity and the comorbidity of MASLD is increasing in children, and this is a medical problem that needs to be addressed urgently. It is well known that children with metabolic associated chronic disease often continue to have these chronic diseases as adults, which leads to reduced life expectancy, quality of life, and increasing healthcare needs and financial burden. The authors of this paper recommend healthy weight reduction not only through lifestyle modification but through obesity pharmacotherapy and bariatric surgery. Therefore, this guidance reviews available therapies to achieve healthy weight reduction and reverse MASLD to prevent progressive liver fibrosis, and metabolic disease.